DEVELOPMENT OF MIDDLE/MTS MATHEMATICS LEARNING MEDIA BASED ON ISLAMIC COMMUNITY CULTURE ACEH BESAR - Marna Aina; Novi Trina Sari (Jurnal Ilmiah Pendidikan dan Pembelajaran Matematika, 2021)
ABSTRACKThe presence of ethno-mathematics in mathematics learning provides a new nuance that learning mathematics is not only confined in the classroom but the outside world by visiting or interacting with local culture can be used as a medium for learning mathematics. The research begins with the activity of exploring and examining the potential for the use of religious and cultural sites (artifacts) as learning media for various mathematics teaching materials at the junior high school level using a qualitative approach followed by research and development (RD) methods following the 4D model at the product trial stage. The stages taken are the define stage, the planning stage, the develop stage and the dissemination stage. Data collection techniques in this study were interviews and questionnaires. Validation is carried out by material experts. Based on the results of the validation of the quality stage of the learning media content, it was obtained an average score of 89.46% with the criteria "very appropriate or very feasible". Based on the results of the research the teacher's response to the media obtained an average score of 4.23 where x 3.25 with the criteria "very good". In the trials of students, an average score of 4.55 was obtained where x 3.25 with the criteria "very good". Based on this assessment, the mathematics learning media material of the Two-Variable Linear Equation System (SPLDV) based on Islamic culture can be used as a learning medium.Keywords: Media Development, Based on Islamic Culture of Aceh Besar Community, 4D ModelABSTRAKHadirnya etnomatematika dalam pembelajaran matematika memberikan nuansa baru bahwa belajar matematika tidak hanya terkungkung didalam kelas tetapi dunia luar dengan mengunjungi atau berinteraksi dengan kebudayaan setempat dapat digunakan sebagai media pembelajaran matematika. Penelitian diawali dengan kegiatan mengeksplorasi dan mengkaji potensi pemanfaatan situs (artifaks) agama dan budaya sebagai media pembelajaran untuk berbagai materi ajar matematika di tingkat sekolah menengah pertama menggunakan pendekatan kualitatif dilanjutkan dengan metode penelitian dan pengembangan (RD) mengikuti model 4D pada tahapan uji coba produk. Tahapan yang dilakukan yaitu tahap pendefinisian (define), tahap perencanaan (design), tahap pengembangan (develop), dan tahap menyebaran (disseminate). Teknik pengumpulan data dalam penelitian ini adalah wawancara dan angket. Validasi dilakukan oleh ahli materi. Berdasarkan hasil validasi tahap kualitas isi media pembelajaran diperoleh skor rata-rata 89,46% dengan kriteria sangat sesuai atau sangat layak. Berdasarkan hasil penelitian respon guru terhadap media diperoleh rata-rata skor sebesar 4,23 dimana x 3,25 dengan kriteria sangat baik. Pada uji coba kepada peserta didik diperoleh rata-rata skor sebesar 4,55 dimana x 3,25 dengan kriteria sangat baik. Berdasarkan penilaian tersebut maka media pembelajaran matematika materi Sistem Persamaan Linear Dua Variabel (SPLDV) berbasis budaya islami dapat dijadikan sebagai media pembelajaran.Kata Kunci: Pengembangan Media, Berbasis Budaya Islami Masyarakat Aceh Besar, Model 4D